Effect of prolonged neck muscle vibration on lateral head tilt in severe spasmodic torticollis. Issue 5 (1st November 2000) - Karnath, H-O; Konczak, J; Dichgans, J
Abstract : Short term vibration of the dorsal neck muscles (10–35 s) is known to induce involuntary movements of the head in patients with spasmodic torticollis. To investigate whether neck muscle vibration might serve as a therapeutic tool when applyed for a longer time interval, we compared a vibration interval of 5 seconds with a 15 minute interval in a patient with spasmodic torticollis with an extreme head tilt to the right shoulder. Head position was recorded with a two camera optoelectronic motion analyzer in six different test conditions. Vibration regularly induced a rapid change of head position that was markedly closer to a normal, upright posture. After 5 seconds of vibration, head position very quickly returned to the initial position within seconds. During the 15 minute interval, head position remained elevated. After terminating vibration in this condition, the corrected head position remained stable at first and then decreased slowly within minutes to the initial tilted position. CONCLUSIONS: (1) In this patient, muscle vibration was the specific sensory input that induced lengthening of the dystonic neck muscles. Neither haptic stimulation nor transcutaneous electrical stimulation had more than a marginal effect. (2) The marked difference in the change of head position after short and prolonged stimulation supports the hypothesis that spasmodic torticollis might result from a disturbance of the central processing of the afferent input conveying head position information—at least in those patients who are sensitive to sensory stimulation in the neck region. (3) Long term neck muscle vibration may provide a convenient non-invasive method for treating spasmodic torticollis at the central level by influencing the neural control of head on trunk position.